Drought effects on the early development stages of Panicum virgatum L.: Cultivar differences - Aimar, Darío Cesar (2014)
We studied the response to moderate drought and re-watering in 55-day-old plants of the lowland cv. Kanlow and the upland cv. Greenville. Plants were grown in a growth chamber; drought treatment was applied by water suppression until moderate stress was reached. The optimal harvest time was determined when the relative water content (RWC) in plants reached an average of 60%. The effects of drought and recovering on growth (i.e. plant height and leaf number), antioxidant enzymes (SOD and CAT), abscisic, salicylic and jasmonic acids levels (ABA, SA, JA), and water stress related genes were analyzed. Drought induced a decrease in growth in cv. Greenville but not in Kanlow. Drought tolerance in cv. Kanlow was correlated with higher antioxidant activities both in stress and recovery. Thus, we investigated stress hormones known to induce reactive oxygen species (ROS). ABA was the main hormone under stress, and increased higher in cv. Kanlow than in cv. Greenville. SA and JA basal levels were higher in well watered plants of cv. Kanlow. At gene levels, RAB18 and RD22 overexpressed after 24 h of re-watering in cv. Kanlow, resembling a “stress memory” mechanism described in other species. Further molecular markers of hormone effects (PR2) or drought (DREB2) well known in dicots seem not to be specific for Panicum virgatum. Overall, we found that cultivar Kanlow has an effective machinery of stress response, which makes it promising to be grown successfully in semi-arid regions.